The 'hard work' of polyamory: ethnographic accounts of intimacy and difference in the Netherlands. Issue 7 (3rd October 2022) - Roodsaz, Rahil
ABSTRACT: The subversive potential of nonmonogamous relationships to provide nonpossessive and meaningful modes of bonding beyond heteropatriarchal monogamous relationships has been a concern of feminist scholarship and activism for more than a century. Focusing on polyamory in the Netherlands, this paper aims to contribute to this scholarship by putting power relations at the centre of analysis. Ethnographic participant observation and in-depth interviews with people in polyamorous relationships show that their experiences of polyamory as emotionally, ethically, and subjectively hard work are deeply entangled with gender, age, class, and racial difference, which is understood as both fluid and as emerging in social contexts. This entanglement of hard work and difference is identified and investigated in three areas: resisting stigmatization, negotiating autonomy and commitment, and managing jealousy. It is argued that although polyamory's appeal to ethical plurality offers possibilities for resisting heteropatriarchal forces in society, its simultaneous reliance on an individualistic therapeutic discourse undermines those very possibilities for resistance, serving an apolitical late-capitalist demand for self-management and -improvement.